Kinerja Serat Ijuk sebagai Tutupan Permukaan Tanah untuk Pengendalian Erosi pada Lereng Pegunungan di Lahan Tanam Jagung - Fikri Maulana Ntobuo; Muhammad Jahja; Muh. Fachrul Latief; Fitryane Lihawa; Meilan Demulawa; Dewa Gede Eka Setiawan (Lembaga Pengembangan Kinerja Dosen, 2026)
Soil erosion is a major problem on sloping land that can reduce soil fertility and agricultural productivity. This study aims to analyze the effectiveness of palm fiber (ijuk) nets and corn plants in controlling soil erosion on land with a slope of approximately 57° in Bina Jaya Village, Tolangohula District, Gorontalo Regency. The method used was a field experiment with three treatments: Plot I (ijuk net + corn), Plot II (ijuk net), and Plot III (without treatment). The observed data included rainfall, soil erosion mass, and corn growth used to calculate the Leaf Area Index (LAI). The results showed that Plot I produced the lowest soil erosion (16.8 kg), followed by Plot II (23.7 kg), and Plot III (84.5 kg). Rainfall had a direct influence on increasing soil erosion, especially on untreated land. Increasing LAI values contributed to reducing erosion by improving soil cover and reducing runoff. The effectiveness of the ijuk net reached 80.1% when combined with vegetation and 71.9% without vegetation. Therefore, the combination of ijuk net and corn plants is proven to be an effective, simple, economical, and sustainable soil conservation method for sloping land.